POTENSI ASAM KLOROGENAT PADA KOPI (COFFEA SP.) SEBAGAI ANTIHIPERGLIKEMIA UNTUK TERAPI SUPORTIF DIABETES MELITUS TIPE 2: TINJAUAN PUSTAKA SISTEMATIS - Rahmah Salsah Hudriyah (2022)
Introduction: Diabetes mellitus type 2 is a pathological condition which defines a persistent elevated total blood glucose. Coffee contains chlorogenic acid which has become a new promising agent to treat hyperglycemia. Objective: This study aims to analyze the potential of chlorogenic acid in coffee as an antihyperglycemic agent in animal and human studies. Method: Systematic literature review method is used based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P). Through electronical searching on several journal databases such as PubMed, ProQuest, ScienceDirect, Google Scholar, and Cochrane journals were obtained. Journals were screened based on inclusions and exclusions criteria and assessed using The Joanna Briggs Institute (JBI) Critical Appraisal tools checklist for human studies and SYRCLE's risk of bias tool for animal studies. Result: 23 journals were analyzed.. The results show there are a total 9 journals that show a significant decrease of blood glucose after ingestion of chlorogenic acid. Conclusion: Chlorogenic acid in coffee shows little potential as an antihyperglycemic agent to become supportive therapy of T2DM. Several factors affect the antihyperglycemic effect include: dosage, coffee roasting process, combination with other compounds, and types of coffee used. Minimum dose of chlorogenic acid in coffee that significantly decrease blood glucose in analyzed journals are 400 mg/kgBW of in animals and 510,6 mg/day in human.